2010
DOI: 10.5194/amt-3-1667-2010
|View full text |Cite
|
Sign up to set email alerts
|

Possible shift of spectral response function of the MODIS 6.8 μm water vapor channel causing a cold bias of 2–3 K

Abstract: Abstract. The calibration of the Moderate-resolution Imaging Spectroradiometer (MODIS) 6.8 µm water vapor (WV) channel was assessed by comparing Terra/MODIS measurements with the WV channel brightness temperatures equivalent to Infrared Atmospheric Sounding Interferometer (IASI) measurements for June 2007 and December 2007. IASI spectral information was transferred to the Japanese Multifunctional Transport Satellite (MTSAT)-1R WV channel and then to the MODIS WV channel. Results indicate that the MODIS WV chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…This study employs the clear‐sky module of the Community Radiative Transfer Model (CRTM) designed for a wide variety of sensors including the Aqua MODIS [ Han et al ., ; Liu and Weng , ]. By comparing the Aqua MODIS IR observations with collocated high spectral resolution observations, such as from AIRS and IASI, some previous studies evaluated the quality of the spectral response functions (SRFs) of the Aqua MODIS IR channels and demonstrated that the Aqua MODIS SRFs are shifted in some water vapor and CO 2 channels [ Tobin et al ., ; Sohn et al ., ]. These shifted SRFs lead to simulation biases up to 2–3 K in terms of brightness temperature (BT).…”
Section: Forward Modelmentioning
confidence: 99%
“…This study employs the clear‐sky module of the Community Radiative Transfer Model (CRTM) designed for a wide variety of sensors including the Aqua MODIS [ Han et al ., ; Liu and Weng , ]. By comparing the Aqua MODIS IR observations with collocated high spectral resolution observations, such as from AIRS and IASI, some previous studies evaluated the quality of the spectral response functions (SRFs) of the Aqua MODIS IR channels and demonstrated that the Aqua MODIS SRFs are shifted in some water vapor and CO 2 channels [ Tobin et al ., ; Sohn et al ., ]. These shifted SRFs lead to simulation biases up to 2–3 K in terms of brightness temperature (BT).…”
Section: Forward Modelmentioning
confidence: 99%
“…Different possible contributions to the observed errors have been mentioned and, according to the referred previous research [8,[94][95][96][97], some of them are more critical than others (e.g., SRF and BRDF related). Consequently, one should not exclude that the total contribution of these factors might be the cause of the resulting, although reduced, mismatches of the cross-calibration of FASat-C.…”
Section: Discussionmentioning
confidence: 99%
“…According to several authors, other possible sources of uncertainty in the calibration of satellite sensors are the variations affecting the SRFs [91][92][93][94][95][96][97]. These factors, which generate biases in measured radiances and in data-derived parameters, are related to changes in the transmittance of filters or optical components and to shifts of the SRFs towards shorter or longer wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…The spectral shift of MODIS SRFs has been suspected as a cause for the discrepancy between MODIS and IASI measurements (Sohn et al, ). The magnitude of the spectral shift for each MODIS band can be determined based on the MODIS‐IASI intercalibration errors shown in Figure , that is, the SRF shifts are optimized to eliminate the bias of MODIS‐IASI difference.…”
Section: Application On Real Airs/modis Datamentioning
confidence: 99%